2018
DOI: 10.3892/mmr.2018.9552
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑339‑5p inhibits cell proliferation of acute myeloid leukaemia by directly targeting SOX4

Abstract: In recent decades, microRNAs (miRNAs) have been considered novel gene regulators. Dysregulated miRNAs serve crucial roles in the formation and progression of acute myeloid leukaemia (AML). Therefore, the roles of differentially expressed miRNAs in AML require extensive investigation to obtain insight into the treatment of patients with AML. The present study demonstrated significant miR-339-5p downregulation in AML samples and cell lines. miR-339-5p overexpression attenuated AML cell proliferation by inducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…What is more, a recent study has reported that SOX4 is a crucial tumorigenic target for C/EBPα mutant AML (Zhang et al, 2013). In addition, AML patients with low SOX4 expression had higher remission rates and longer overall survival than AML patients with high SOX4 expression, therefore the expression of SOX4 could act as a biomarker for the clinical prognosis of AML patients(Lu et al, 2017; Sun et al, 2018). In the present study, we found that a binding relationship between SOX4 and ARHGAP9 promoter, and the expression level of ARHGAP9 could be regulated by SOX4.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, a recent study has reported that SOX4 is a crucial tumorigenic target for C/EBPα mutant AML (Zhang et al, 2013). In addition, AML patients with low SOX4 expression had higher remission rates and longer overall survival than AML patients with high SOX4 expression, therefore the expression of SOX4 could act as a biomarker for the clinical prognosis of AML patients(Lu et al, 2017; Sun et al, 2018). In the present study, we found that a binding relationship between SOX4 and ARHGAP9 promoter, and the expression level of ARHGAP9 could be regulated by SOX4.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a kind of noncoding RNAs with 21–25 nucleotides which regulate gene expression through posttranscription regulation or degradation messenger RNA (mRNA) of target gene 13 . miRNA dysregulation is associated with the occurrence and progression of multifarious cancers, 14,15 including AML 16 . MicroRNA‐625 (miR‐625) has been reported to be downregulated and might serve as a tumor suppressor in pediatric AML 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…13 miRNA dysregulation is associated with the occurrence and progression of multifarious cancers, 14,15 including AML. 16 MicroRNA-625 (miR-625) has been reported to be downregulated and might serve as a tumor suppressor in pediatric AML. 17,18 Sex-determining region Y-related high mobility group box (SOX) genes can bind to DNA in a sequence-specific manner and are highly conserved throughout evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Castro‐Oropeza et al demonstrated that LncRNA DANCR competed with Sox4 mRNA to bind with miR‐138, thereby affecting the expression of Sox4 . Sun et al found that miR‐339‐5p directly targeted SOX4 and exerted anti‐proliferative effects in acute myeloid leukaemia (AML). Yang et al found that lncRNA ARNILA acted as a competitive endogenous RNA to promote SOX4 by supporting mir‐204 in triple‐negative breast cancer.…”
Section: Introductionmentioning
confidence: 99%